PARENTAL IMPRISONMENT AND CHILDRENS RIGHTS - Parkes, Aisling; Donson, Fiona J. L. (ABINGDON : ROUTLEDGE, 2021)
This book brings together internationally renowned academics and professionals from a variety of disciplines who, in a variety of ways, seek to understand the legal, conceptual and practical consequences of parental imprisonment through a children's rights lens. Children whose parents have been incarcerated are often referred to as "invisible victims of crime and the penal system." It is well accepted that the imprisonment of a parent, even for a short period of time, not only negatively affects the lives of children but it can also result in a gross violation of their fundamental human rights, such as the right of access to their parent and the right to have an input into decision-making processes affecting them, the outcomes of which will without doubt affect the life of the child concerned. This collection foregrounds the voice of these children as it explores transdisciplinary boundaries and examines the practice and development of the rights of both children and their families within the wider dynamic of criminal justice and penology practice. The text is divided into three parts which are dedicated to 1) hearing the voices of children with parents in prison, 2) understanding to what extent children's rights informs prison policy, and 3) demonstrating how law in the form of children's rights can help frame both court sentencing and prison practice in a way that minimises the harm that contact with the prison system can cause. The research drawn upon in this book has been conducted in a number of European countries and demonstrates both good and bad practice as far as the implementation of children's rightsis concerned in the context of parental incarceration. An accessible and compelling read, this book will appeal to students and scholars of law, children's rights, criminology, sociology, social work, psychology, penology and all those interested in, and working towards, protecting the rights of children who have a parent in prison.
OCLC-licensed vendor bibliographic record.
Keywords: Children of prisoners; Prisoners -- Family; Children's rights; SOCIAL SCIENCE / Criminology